Digital dead-beat and repetitive combined control for stand-alone four-leg VSI - Lidozzi, Alessandro; Solero, Luca; Crescimbini, Fabio; Ji, Chao; Zanchetta, Pericle (2016)
This paper deals with a newly conceived combine control topology. Dead-Beat and Repetitive controllers are proposed to operate jointly in 4-leg VSI for stand-alone applications. In such mode of operation, dedicated controller has to regulate the inverter output voltages, which are measured at the output of the power filter. Each control topology exhibits some specific features. Dead-Beat can rapidly compensate output voltage variations due to load changes; on the contrary, Repetitive Control can provide the required harmonic compensation capabilities that are mandatory to comply with the Standards, when balanced and unbalanced non-linear loads have to be fed.